2015
DOI: 10.2166/wcc.2015.050
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of potential impacts of climate and land use changes on stream flow: a case study of the Nam Xong watershed in Lao PDR

Abstract: water is transferred to the Nam Ngum Reservoir. Here, stream flow will decrease by 11.7-12.2%; the overall figure for the watershed is 0.7-1.9%. Our results indicate that water management in the middle part of the Nam Xong watershed should be carefully considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 11 publications
1
16
0
Order By: Relevance
“…There are 12 studies out of the 126 reviewed articles (Table 1) that reported applications of combined climate change and land use change impacts on SEA watersheds. These studies were conducted in Indonesia [87,93], Lao PDR [96], Malaysia [104], Myanmar [112], Thailand [49,117], Vietnam [147,154,155], and also the 3S river basin [63]. Basically, the SWAT-based combined climate change and land use change impact assessment can be divided into two main groups: (1) Consider only the historical climate and land use pattern; and (2) incorporation of future climate and land use projections into the SWAT model.…”
Section: Swat Studies On Climate Change and Land Use Changementioning
confidence: 99%
See 1 more Smart Citation
“…There are 12 studies out of the 126 reviewed articles (Table 1) that reported applications of combined climate change and land use change impacts on SEA watersheds. These studies were conducted in Indonesia [87,93], Lao PDR [96], Malaysia [104], Myanmar [112], Thailand [49,117], Vietnam [147,154,155], and also the 3S river basin [63]. Basically, the SWAT-based combined climate change and land use change impact assessment can be divided into two main groups: (1) Consider only the historical climate and land use pattern; and (2) incorporation of future climate and land use projections into the SWAT model.…”
Section: Swat Studies On Climate Change and Land Use Changementioning
confidence: 99%
“…Sayasane et al [96] studied the Nam Xong watershed located in Lao PDR, with consideration of future land use and climate changes. Future land use was produced by using statistical analysis of historical land use trends between 1997 and 2008, while future climate was generated from the PRECIS model [96]. They found that the future streamflow will decrease by 11.7 to 12.2% over the next 20 years, especially in the middle part of the basin.…”
Section: Swat Studies On Climate Change and Land Use Changementioning
confidence: 99%
“…Liu et al, 2015) and scenarios that reflect hypothetical shifts between various percentages of urban, forest, agricultural and other land use (Zhang et al, 2015(Zhang et al, , 2016Wu et al, 2015). Similar types of combined SWAT climate change/land use change studies have been performed in other regions including Asia (Sayasane et al, 2015;Singkran et al, 2015;Tan et al, 2015), Europe (Serpa et al, 2015;Mehdi et al, 2015b;Guse et al, 2015) and North America (Mehdi et al, 2015a;Neupane and Kumar, 2015;Goldstein and Tarhule, 2015).…”
Section: Introductionmentioning
confidence: 95%
“…This indicates that both these models exhibit high performance in humid (vs. arid) regions, which concurs with the results of many other studies (a summary of these studies is shown in Table Ⅶ). In some of these studies (Zolghadr et al, 2018;Sayasane et al, 2016), it was put forward that model weakness in arid regions compared to humid regions may be the result of rainfall intensity and distribution in arid regions.…”
Section: Comparing the Models Performance According To Climatementioning
confidence: 99%